Phytosociological Analysis and Distribution Pattern of Understorey Vegetation in Differently Managed Quercus leucotrichophora Forests along the Elevation Gradient in North- Western Himalaya, India. - Rai, Pradeepen; Kikon, Grace (Indian Forester, 2018)
Two differently managed Quercus leucotrichophora forests viz. Reserved Forest (RF) and Protected Forest (PF) were selected at Rajgarh Forest Division in Himachal Pradesh. These selected forests were further delineated into three elevations ranges as; E <1 1650 m, E2 = 1651 to 1900 m and E3>1900 m for enumeration to understand the effect of management and altitudinal gradient on phytosociological attributes and community structure. Total density and total basal area of shrubs and herbs was recorded higher under Q. leucotrichophora reserved forest as compared to protected forest. However, no definite pattern of change was observed in its total density and basal area along the elevation for both shrubs and herbs components. Reserved forest had Myrisine-Daphne, Strobilanthes- Rubus and Boenninghausenia-Carissa while, protected forest had Boenninghausenia-Daphne, Strobilanthes-Myrsine, Daphne-Sarcococca as dominant shrubs communities at elevations E1, E2 and E3, respectively. Likewise, herbage communities at reserved forest had Viola-Heteropogon, Viola-Cyperus and Malaxis-Viola while protected forest had Bidens- Imperata, Oplismenus-Digiteria and Digiteria-Oplismenus at respective E1, E2 and E3 elevations. The understorey species was found to have wide ecological amplitude influencing dominance and performance greatly as reflected by quantitative features such as density, basal area, frequency, A/F ratio and importance value index. Regular distribution was more prominent than contagious and random distribution depicting existence of severe competition between the individual species. Higher values of phytosociological attributes in reserved forest could be ascribed to higher degree of protection and management strategies adopted which wasn’t the case in protected forest.